The Relationship Between Campus Sports Participation and Academic Achievement Among University Students - Hudain, Muh. Adnan (SHOOTING: Journal of Sport, Health, and Education, 2025)
This study examines the relationship between participation in campus sports activities and academic achievement among university students. The research employed a quantitative approach using correlational design with 250 university students as participants. Data were collected through questionnaires measuring sports participation levels and academic performance indicators including GPA, attendance rates, and time management skills. Results indicate a significant positive correlation (r = 0.742, p < 0.01) between sports participation and academic achievement. Students who actively participated in campus sports demonstrated higher GPAs (3.45 ± 0.52) compared to non-participants (2.98 ± 0.48). The study also revealed that sports participation enhances discipline, time management, and stress management skills, which contribute to better academic performance. These findings suggest that universities should encourage and facilitate student participation in sports activities as part of holistic education development. The research contributes to understanding the multifaceted benefits of sports participation in academic environments and provides evidence for policy makers to integrate sports programs into university curricula.